2022
DOI: 10.3389/fneur.2022.994341
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hemoglobin and triglycerides in moyamoya disease: A cross-sectional study

Abstract: Hemoglobin (Hb) and lipid metabolism are critical in the pathophysiology of moyamoya disease (MMD), and Hb and triglycerides (TGs) both play roles in the development of cerebrovascular illness. However, there is little evidence of a link between Hb and TGs in patients with MMD. This study aimed to determine the association between Hb and TGs in patients who had recently been diagnosed with MMD. From March 2013 to December 2018, 337 patients clinically diagnosed with MMD were admitted to our hospital. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Early prevention of hyperuricemia and lipid abnormalities has been shown to decrease the occurrence of MMD. However, the exact connection between Hb and TG in the pathology of MMD is not fully understood [36]. Shifu Li et al's study revealed that molecular biology and next-generation sequencing technologies have improved our understanding of disease mechanisms at the genetic and mRNA levels.…”
Section: Pathophysiology Of Moyamoya Diseasementioning
confidence: 99%
“…Early prevention of hyperuricemia and lipid abnormalities has been shown to decrease the occurrence of MMD. However, the exact connection between Hb and TG in the pathology of MMD is not fully understood [36]. Shifu Li et al's study revealed that molecular biology and next-generation sequencing technologies have improved our understanding of disease mechanisms at the genetic and mRNA levels.…”
Section: Pathophysiology Of Moyamoya Diseasementioning
confidence: 99%
“…According to new research ( 14 ), systemic inflammation is crucial to myofibrosis, disease progression, and the pathogenesis of uterine smooth muscle tumours. The relationship between systemic inflammation and lipids has been demonstrated in a variety of diseases ( 15 , 16 ), but its relationship in patients with newly diagnosed uterine fibroids has not been clarified. This study investigated whether there was a correlation between inflammatory markers and triglycerides in patients with UL by analysing clinical data from newly diagnosed UL patients.…”
Section: Introductionmentioning
confidence: 99%